Pertukaran Sosial pada Masyarakat Petambak: Kajian Struktur Sosial Sebuah Desa Kawasan Pertambakan di Sulawesi Selatan - Darmawan Salman; Andin H. Taryoto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1992)
An important aspect of society in brackish water agro-ecosystem is the nature of social exchange between each party found in the social system. This is very much related to various social status in that society. An analysis on social exchange pattern will be important to identify which linkages that might lead to a more integrative social structure. With a case study of a brackish-based society in South Sulawesi, the analysis is directed toward a